Corporate Responsibilities on The Action of Human Trafficking Criminals in Indonesia - Muh Abdul Qudus; Nyoman Serikat Putra Jaya (Hang Tuah Law Journal, 2019)
Problems related to human rights in Indonesia are criminal acts of human trafficking committed by corporations. Trafficking in persons is a modern form of human slavery and is also one of the worst forms of treatment of violations of human dignity. However, the development has difficulties with law enforcement related to corporations that commit criminal acts of trafficking. The research method used is a normative juridical research method using secondary data to be analyzed qualitatively. The results of this study show that corporations as subjects of criminal law can be equated with humans, because there are rights and obligations given by law and therefore corporate skills are also equated with human skills. Regulations regarding corporate responsibility are regulated in Law Number 21 of 2007 concerning Eradication of Criminal Act of Human Trafficking, corporations can be held liable if they commit criminal acts of trafficking by fulfilling the requirements of criminal liability in general such as the ability to be responsible, mistakes and intentions, absence of matters that are used as reasons for criminal offenses.